1990
DOI: 10.1002/jnr.490260306
|View full text |Cite
|
Sign up to set email alerts
|

Neural influences on synovial mast cell density in rat

Abstract: The mast cell, an immunocompetent cell that contributes to neurogenic inflammation in a variety of tissues, including synovium, is found in close proximity to peripheral terminals of unmyelinated primary afferents and sympathetic postganglionic nerve terminals. In this study we evaluated the hypothesis that the density of mast cells in synovial tissue is dependent on the neural innervation. In normal rats, we found that the density of mast cells in the ankle joint capsule, which is heavily innervated, is great… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…Although such proximity might occur at random, in vitro co-culture studies have shown the formation of specific contacts between rat sympathetic neurons and mast cell (Blennerhassett and Bienenstock 1990;Blennerhassett et al 1991), and chemical sympathectomy produced by guanethidine treatment reduced the synovial mast cells density in vivo (Levine et al 1990). Functional studies indicate a bilateral interaction between mast cells and sympathetic axons.…”
Section: Dermal Blood Vesselsmentioning
confidence: 99%
“…Although such proximity might occur at random, in vitro co-culture studies have shown the formation of specific contacts between rat sympathetic neurons and mast cell (Blennerhassett and Bienenstock 1990;Blennerhassett et al 1991), and chemical sympathectomy produced by guanethidine treatment reduced the synovial mast cells density in vivo (Levine et al 1990). Functional studies indicate a bilateral interaction between mast cells and sympathetic axons.…”
Section: Dermal Blood Vesselsmentioning
confidence: 99%
“…The patients suffer from frequency of urination and pain which is relieved by voiding. It has been shown recently that the innervation in the synovial joint of the rat, by unmyelinated afferent and sympathetic efferent fibres, exerts a tropic effect on mast cell density (Levine et al, 1990). The classic form of IC (Hunner's ulcer) is characterised by a high density of mast cells in the bladder wall (Aldenborg et al, 1986).…”
mentioning
confidence: 99%
“…However, it is also possible that the vitamin D deficient diet may have resulted in mast cell degranulation, which reduced the number of resident neurturin-ir mast cells. While we cannot rule out the possibility that the reduction in mast cells occurs secondary to the loss of innervation, as has been previously suggested (Levine et al, 1990a), the most straightforward explanation is that non-peptidergic axons were reduced in VD- rats in response to a decrease in neurturin-synthesizing mast cells.…”
Section: 0 Discussionmentioning
confidence: 67%
“…Mouse anti-CD163 was used at a dilution of 1:500 (AbD Serotec (Damm et al, 2011)). Mast cells are also present within the synovium where they are intimately associated with nerves, and their density has been correlated with synovial innervation density (Levine et al, 1990a, Hukkanen et al, 1991). Mouse anti-mast cell tryptase (MCT) diluted 1:250 (Abcam (Walls et al, 1990)) was used as a mast cell marker.…”
Section: Methodsmentioning
confidence: 99%